Antioxidant and antimicrobial activities of Penicillium sp. lectins - Singh Ram S.; Walia Amandeep K. (Archives of Biological Sciences, 2019)
Lectins are a diverse group of proteins of non-immune origin that interact specifically with glycans. Owing to their specificity, they can mediate various cellular and molecular recognition processes. To explore information on biological activities of lectins from Penicillium duclauxii, P. proteolyticum and P. griseoroseum, they were investigated for their antioxidant and antimicrobial activities. Penicillium sp. lectins exhibited moderate antioxidant activity. P. duclauxii, P. proteolyticum and P. griseoroseum lectins inhibited DPPH with an IC50 value of 71.42, 75.04 and 82.11 μg/mL, respectively. P. duclauxii, P. proteolyticum and P. griseoroseum lectins inhibited the hydrogen peroxide radical with IC50 values of 198.57, 209.76 and 215.31 μg/mL, respectively. P. duclauxii and P. proteolyticum lectins exhibited potent antibacterial activity against Gram-negative bacteria. P. griseoroseum lectin inhibited only Gram-positive bacteria. Penicillium sp. lectins did not exhibit antifungal activity. The biological potential of Penicillium sp. lectins will help to understand their biomedical applications. This is the first report on the antioxidant and antimicrobial activities of purified lectins from Penicillium sp.